Dysregulation of AKT Pathway by SMYD2-Mediated Lysine Methylation on PTEN - Makoto Nakakido; Zhenzhong Deng; Takehiro Suzuki; Naoshi Dohmae; Yusuke Nakamura; Ryuji Hamamoto (Neoplasia: An International Journal for Oncology Research, 2015)
Phosphatase and tensin homologue (PTEN), one of the well-characterized tumor suppressor proteins, counteracts the phosphatidylinositol 3-kinase-AKT pathway through its unique lipid phosphatase activity. The functions of PTEN are regulated by a variety of posttranslational modifications such as acetylation, oxidation, ubiquitylation, phosphorylation, and SUMOylation. However, methylation of PTEN has not been reported so far. In this study, we demonstrated that the oncogenic protein lysine methyltransferase SET and MYND domain containing 2 (SMYD2) methylates PTEN at lysine 313 in vitro and in vivo. Knockdown of SMYD2 suppressed the cell growth of breast cancer cells and attenuated phosphorylation levels of AKT, indicating that SMYD2-mediated methylation negatively regulates PTEN tumor suppressor activity and results in activation of the phosphatidylinositol 3-kinase-AKT pathway. Furthermore, PTEN protein with lysine 313 substitution diminished phosphorylation of PTEN at serine 380, which is known to inactivate tumor suppressor functions of PTEN. Taken together, our findings unveil a novel mechanism of PTEN dysregulation regulated by lysine methylation in human cancer.